2010
DOI: 10.1345/aph.1m657
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Prescribing Predicts Adverse Drug Events in Older Adults

Abstract: Implicit measurement of actual inappropriate prescribing predicted ADE risk, an important clinical outcome. This finding helps confirm the validity of prior studies that have relied on explicit measures to link potentially inappropriate prescribing to adverse health outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
140
2
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 184 publications
(151 citation statements)
references
References 23 publications
5
140
2
4
Order By: Relevance
“…However, the two published studies on the predictive validity of the MAI both indicate that this tool can reliably predict clinical patient outcomes [33,34]. Lund et al showed that inappropriate prescribing, according to a modified MAI score [33], is associated with adverse drug events in older men, and Schmader et al demonstrated an association between worse MAI scores and poorer blood pressure control and use of more health services [34].…”
Section: Discussionmentioning
confidence: 99%
“…However, the two published studies on the predictive validity of the MAI both indicate that this tool can reliably predict clinical patient outcomes [33,34]. Lund et al showed that inappropriate prescribing, according to a modified MAI score [33], is associated with adverse drug events in older men, and Schmader et al demonstrated an association between worse MAI scores and poorer blood pressure control and use of more health services [34].…”
Section: Discussionmentioning
confidence: 99%
“…Although polypharmacy has no generally accepted definition, most often it is defined by cut-offs, in terms of the number of medications taken, ranging from two to ten (9)(10)(11)(12). However, regardless of the definition, its prevalence has been reported to rise with age, and is associated with an increased risk of inappropriate drug prescription, under-use of effective treatment, medication errors, poor adherence to pharmacological therapies, drug/drug and drug/disease interactions, and adverse effects (3,(13)(14)(15)(16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of adverse drug reactions (ADRs) rises exponentially rather than linearly with the number of drugs taken, and advanced age and polypharmacy are associated with a substantial increase in the risk of ADRs (4,10,15,(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[8][9][10][11][12] Inappropriate prescribing, as indicated by explicit criterion-based or implicit judgment-based measures, increases the occurrence of adverse drug events. 9,10,[13][14][15] Therefore, the identification of inappropriate prescribing is important, as it can allow avoidance of preventable adverse drug events and optimization of pharmacotherapy for the frail older individual.…”
Section: Introductionmentioning
confidence: 99%